1998
DOI: 10.1046/j.1360-0443.1998.9368779.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking cessation counseling on recovery from alcoholism: findings from a randomized community intervention trial

Abstract: Counseling alcoholics in treatment to quit smoking does not jeopardize the alcohol recovery process. However, low-intensity tobacco interventions are unlikely to yield high tobacco quit rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 17 publications
7
95
2
6
Order By: Relevance
“…With the possible exception of a study by Joseph et al (2004), this has not seemed to occur (e.g., Hurt et al, 1994;Burling et al, 1991;Burling et al, 2001;Bobo et al, 1995Bobo et al, , 1998. Inconsistencies among outcome studies, however, suggest a need for further evaluation of concurrent smoking cessation treatment on alcohol treatment outcome.…”
mentioning
confidence: 95%
“…With the possible exception of a study by Joseph et al (2004), this has not seemed to occur (e.g., Hurt et al, 1994;Burling et al, 1991;Burling et al, 2001;Bobo et al, 1995Bobo et al, , 1998. Inconsistencies among outcome studies, however, suggest a need for further evaluation of concurrent smoking cessation treatment on alcohol treatment outcome.…”
mentioning
confidence: 95%
“…When alcoholics are compared across various stages of their disease, individual quit attempts result in quit rates of 3-19% at 4-6 months while in alcoholism treatment (Bobo et al, 1996;Bobo et al, 1998;Grant KM, 2003;Joseph et al, 2004;Kalman et al, 2001) and 9-29% at 4-6 months in alcoholics who reported they were no longer drinking (Hays et al, 1999;Kalman et al, 2006;Martin et al, 1997) (Table 1).…”
Section: Previous Studies Of Smoking Cessation In Alcoholicsmentioning
confidence: 99%
“…However, sequential or delayed smoking cessation treatment is rarely delivered under current systems of care, arguing for the need to deliver smoking cessation concurrently with alcohol treatment. One body of work suggests that concurrent smoking cessation treatment does not adversely affect alcohol outcomes, and perhaps, results in improved alcohol outcomes (Bobo et al 1996;Bobo et al 1998;Kalman et al 2001;Prochaska et al 2004). However, in suggesting that concurrent smoking cessation treatment adversely affects alcohol treatment outcomes, recent results from the Timing of Alcohol and Smoking (TASC) randomized controlled trial stand in contrast to these findings (Joseph et al 2004).…”
Section: Introductionmentioning
confidence: 99%